# If the first and the nth term of a G.P. are a and b, respectively, and if P is the product of n terms, prove that P2 = (ab)n.

Given: Let the first and the nth term of a G.P. be a and b, respectively, and P be the product of n terms.

Here,

a1 = a = a

an = b = arn-1 —1

Here,

P = Product of n terms

P = (a) × (ar) × (ar2) × ….. × (arn-1)

P = (a × a × …a) × (r × r2 × …rn-1)

P = an × r 1 + 2 +…(n–1) —2

Here,

1, 2, …(n – 1) is an A.P.

The sum of n terms of an A.P is given by : (here n: no of terms, a:first term, d:common difference)

1+2+3+.+(n-1) =

1+2+3+….+(n-1) =

P = an × r 1 + 2 +…+(n–1)

P = an ×

P2 =

P2 =

P2 =

P2 =

P2 = from eq –1

P2 = (ab)n

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Interactive quiz on inequalities involving AM and GM45 mins
Check Your progress Part 2| Interactive Quiz: Sequence & Series47 mins
Sequence & Series (Lecture 1)56 mins
Sequence & Series (Lecture 5)42 mins
Sequence & Series (Lecture 7)37 mins
Trigonometric Series45 mins
Use of sigma in finding sum42 mins
Quick Recap lecture of Sequence & Series56 mins
General Term of Miscellaneous progression46 mins
Improve your understanding of AP & GP27 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses